Ultraviolet Photoprocessing of Glycine Adsorbed on Various Space-Relevant Minerals - Poggiali, Giovanni; Fornaro, Teresa; Potenti, Simone; Corazzi, Maria Angela; Brucato, John Robert (Frontiers in Astronomy and Space Sciences, 2020)
The discovery of amino acids such as glycine on meteorites and comets confirms the role of small bodies as transport and delivery vehicles of building blocks of life on Earth and possibly on other planetary bodies of our Solar System. Glycine is quite interesting because it is the simplest of the 20 biogenic amino acids, from which complex organic molecules might have originated in our evolved Solar System. To investigate the possible chemical evolution of this molecule in space, it is important to consider how the interaction with mineral matrices influences its photostability. Indeed, the presence of minerals can mediate the effects of electromagnetic radiation, catalyzing photoreactions, or protecting molecules against degradation. Such interactions are responsible for the preservation/degradation mechanisms of organic molecules in space environments. Laboratory simulations of UV processing may provide key insights into the survival of organic molecules in space environment and rocky surfaces, which is of particular relevance for current missions of sample return from asteroids, such as NASA OSIRIS-REx and JAXA Hayabusa 2, and in particular, upcoming space exploration missions on planetary surfaces, such as ESA-Roscosmos ExoMars 2022 and NASA Mars 2020. In this article, we report a laboratory study of UV irradiation of glycine adsorbed on various space relevant minerals: forsterite, antigorite, spinel, and pyrite. We monitored possible changes of glycine functional groups due to UV irradiation through in situ infrared (IR) spectroscopic analysis. Results show that degradation of glycine occurs with a half-life of 0.5–2 h depending on the mineral substrate. Appearance of new IR bands suggests the occurrence of catalytic reactions mediated by minerals and UV.